Pengolahan Kopi Menjadi Kompos: Analisis Proses Pembuatan Kompos dan Digital Marketing - Lailatul Fitri Dwi Rahmawati; Indah Respati Kusuma Sari (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
In Indonesia, the use of inorganic fertilizers is one area that is produced continuously to be used to increase crop yields, especially vegetables. Organic fertilizer and compost also have long-term benefits because they can increase the fertility of plants such as coffee. Indonesia is a coffee producer with unique characteristics. There is one type of coffee that is not widely known by the Indonesian people, namely Excelsa coffee. Excelsa coffee has very distinctive characteristics and aroma. Most of Wonomerto's residents have agricultural land and livestock that can produce coffee and livestock. However, villages that have cattle farms are still unable to utilize animal waste properly, and also residents who have coffee production only process it into ground coffee. Therefore, educational events and new programs for the Bokashi compost coffee market are being held. Apart from that, agricultural products and animal products that cannot yet be processed can be used as organic fertilizer using EM4 technology. The benefits of bokashi fertilizer are that it can increase the nutrient content of plants, reduce organic waste, and encourage the growth of plant microorganisms.